Medical Student Progress Examination Performance and Its Relationship With Metacognition, Critical Thinking, and Self-Regulated Learning Strategies. (February 2021) - Chang, Chi; Colón-Berlingeri, Migdalisel; Mavis, Brian; Laird-Fick, Heather S.; Parker, Carol; Solomon, David
Abstract : Purpose: Metacognition and critical thinking are essential for academic success. The relationship between these components and medical student learning, as assessed with progress examinations, informs curriculum development and efforts to ensure learning progression of all students. This study assessed learning mechanisms by modeling medical students' progress test performance longitudinally at Michigan State University College of Human Medicine. Method: Medical students' (n = 184) medical knowledge was assessed 5 times from fall 2017 through spring 2019 using the Comprehensive Basic Science Examination (CBSE). Structural equation modeling was conducted to investigate associations between 3 latent structures—metacognitive awareness, critical thinking, and self-regulation—and their relationship with students' initial CBSE scores and growth in such scores. The authors measured metacognitive knowledge and regulation by the Metacognitive Awareness Inventory, critical thinking skills by the Watson-Glaser Critical Thinking Appraisal, and self-regulation by the Learning and Study Strategies Inventory. Results: Students' aggregate performance on 5 CBSE scores grew 31.0% the first semester, 16.5% the second semester, 30.1% the third semester, and 22.4% the last semester. Critical thinking had a significant positive relationship with initial performance ( 1.956, P < .001), self-regulation had a significant positive relationship with growth ( 3.287, P < .05), and metacognitive awareness had a negative relationship with growth of student performance in the progress test ( −3.426, P < .01). Conclusions: This structural equation framework is useful for examining the relationships among 3 latent structures—critical thinking, metacognition, and self-regulation—and their relationships with students' progress scores in academic achievement. The initial status of progress examination scores was explained by students' critical thinking ability, but their learning growth on the progress scores was explained by their self-regulation and metacognitive ability. These findings help explain student performance on standardized progress examinations and can aid in interventions to promote student success. Abstract : Supplemental Digital Content is available in the text.